Foley Plus Oxytocin Compared With Oxytocin for Induction After Membrane Rupture: A Randomized Controlled Trial. Issue 1 (January 2018) - Mackeen, A. Dhanya; Durie, Danielle E.; Lin, Monique; Huls, Christopher K.; Qureshey, Emma; Paglia, Michael J.; Sun, Haiyan; Sciscione, Anthony
Abstract : OBJECTIVE: To evaluate the use of a transcervical Foley catheter plus oxytocin infusion compared with oxytocin infusion alone for labor induction and cervical ripening in women 34 weeks of gestation or greater with prelabor rupture of membranes. METHODS: This is a randomized, multicenter trial of women with a live, singleton gestation at 34 weeks of gestation or greater with prelabor rupture of membranes, an unfavorable cervical examination (less than 2 cm or 80% effaced), and no contraindication to labor. Participants were randomly allocated to a transcervical Foley catheter inflated to 30 cc with concurrent oxytocin infusion or oxytocin infusion alone. Oxytocin administration was standardized across sites. The primary study outcome was interval from induction to delivery. To detect a 2.5-hour difference in the interval from induction to delivery, we required outcome data on 194 women, assuming 80% power and a two-tailed α of 5%. Analysis was by intent to treat. RESULTS: We enrolled 201 women: 93 were allocated to Foley and 108 to oxytocin. Demographics were similar between the groups. Time to delivery was not significantly different between groups: in the Foley group, it was 13.9 hours (±6.9 SD) compared with 14.4 hours (±7.9 SD) in the oxytocin group ( P =.69). There were more cases of clinical chorioamnionitis (8% compared with 0%, P <.01) in the Foley group compared with the oxytocin group. There were no differences for other infectious morbidities or any other variable studied. CONCLUSION: In patients with prelabor rupture of membranes, the use of a transcervical Foley catheter in addition to oxytocin does not shorten the time to delivery compared with oxytocin alone, but may increase the incidence of intraamniotic infection. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01973036. Abstract : The use of a transcervical Foley catheter does not shorten the time to delivery for women with an unfavorable cervix undergoing oxytocin labor induction after membrane rupture.